A Study on Cu Thin-Film Electroplated TiO2 Photoanodes for Applications in Natural Dye-Sensitized Solar Cells - M. D. P. A. Shakya; K. M. D. C. Jayathilaka; W. T. R. S. Fernando; W. T. M. A. P. K. Wanninayake; L. S. R. Kumara; O. Seo; J. Tang; O. Sakata; W. P. Siripala; R. P. Wijesundera (Crystals)
Improving the performance of TiO2 photoanodes via the inclusion of metal particles on the electrode surface could provide significant advantages for the development of dye-sensitized solar cells (DSSCs). We studied a TiO2/Cu film electrode prepared by electrodepositing Cu particles on a TiO2 film on an indium-doped tin oxide (ITO) substrate. Cu particles were electrodeposited on a TiO2 electrode at −700 mV vs. a Ag/AgCl electrode in an acetate bath, with the pH adjusted between 6.3 and 7.7 in 0.2 increments to optimize the deposition conditions. TiO2/Cu thin-film electrodes were tested as a photo anode in a natural DSSC consisting of a carbon counter electrode, Vitis vinifera dye, and a KI/I2-based electrolyte. Film characterization was performed using hard X-ray photoelectron spectroscopy (HAXPES), grazing incidence X-ray diffraction (GIXD), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, electrochemical impedance spectroscopy (EIS), ultraviolet–visible spectroscopy (UV–Vis), and photocurrent density–voltage (J–V) measurements. DSSCs with Cu particles containing TiO2 electrodes prepared using an acetate bath of pH 7.3 resulted in a 370% improvement in efficiency compared to the DSSCs without Cu particles. Thus, this study revealed that incorporating Cu particles into the surface of the TiO2 electrode enhances the photovoltaic performance of DSSCs.